Structure and psychometric properties of the maslach burnout inventory in Croatian nurses (Journal of Health Sciences, 2021)
Introduction: The role of nurses in healthcare is of great importance for the well-being of patients. Nurses are exposed to daily stress in the workplace due to the lack of staff, irregular working hours, and lack of support from the management. Such conditions greatly affect the emotional and psychological health of nurses. This study aims to explore the factor structure of the Maslach Burnout Inventory (MBI) on the Croatian sample of nurses.Methods: A cross-sectional study on the sample of 119 nurses, using the MBI scale to assess burn-out in nurses.Results: The reliability of individual subscales expressed by Cronbach’s alpha coefficients showed that all three scales meet the criterion of internal consistency of 0.832. The obtained coefficients of internal consistency are 0.860 for the dimension of emotional exhaustion, 0.809 for the dimension of depersonalization, and 0.791 for the dimension of personal accomplishment.Conclusion: According to this research and comparative research results, we can conclude that MBI 22 can be applied as a valid and reliable burn-out assessment indicator among nursing staff.